Pengendalian Volume Tangki Menggunakan LabVIEW dan Arduino UNO - Ardilessi A (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2015)
Abstract - Rapid technological developments in contemporary times also affected the development of the toolsin an industry.Equipment in an industry that was once driven manually by humans are now beginning to be controlled automatically. One of the automatic controller system that is widely used in an industrial controller system is proportional integral derivative (PID). PID controller consists of three kinds of methods that the controller proportional controller, the integral controller, and derivative controller. Controlling the height levels of the system is done through LabView 2013. Arduino UNO board is used to process the data on the flow sensor and height sensor.Data obtained from the height sensor and flow sensor is used to set the input and output water tank so that the water level in accordance with the desired height. From the test results, using Ti as an input parameter in the integral action zigler – Nichols method. Condition stable and constant oscillation at the output level elevation will be obtained, when the conditions given parameter value Ti is getting bigger and parameter values Kp given increasingly smaller. By using the parameters obtained from the calculation using the method zigler – Nichols, obtained results faster output stable when using a PI controller. Keyword : Controller, Proportional Integral Derivative, Ziegler-Nichols, LabView